Religiosity as a predictor of integrity, work ethics, and organisational commitment: Implications for public administration - Mohd Mahudin, Nor Diana; M. Noor, Noraini; Dzulkifli, Mariam Adawiah; Janon, Nazariah Shar'ie (Jabatan Perkhidmatan Awam Malaysia, 2017)
Research has documented positive relationships between religiosity with physical and mental health, healthy lifestyle, and life satisfaction. Few studies, however, have examined its relationship with occupational behaviour constructs, particularly within the public service and administration. Using a newly-developed religiosity scale, the present study tested the hypothesis that employee religiosity positively predicts higher integrity, stronger work ethics, and greater organisational commitment. Structural equation modelling, using data from a sample of 315 employees from a local university, provided support for the model. The results also indicated the importance of understanding that religiosity and integrity are two distinctive yet interconnected concepts. The implications of the findings are discussed in the context of public service delivery and the extent to which religiosity actually influenced the performance of daily work.